Epigenetic regulation of human FOXP3+ Tregs: from homeostasis maintenance to pathogen defense - Yue, Yi; Ren, Yuqing; Lu, Chunya; Li, Ping; Zhang, Guojun (Frontiers in Immunology, 2024)
Regulatory T cells (Tregs), characterized by the expression of Forkhead Box P3 (FOXP3), constitute a distinct subset of T cells crucial for immune regulation. Tregs can exert direct and indirect control over immune homeostasis by releasing inhibitory factors or differentiating into Th-like Treg (Th-Treg), thereby actively contributing to the prevention and treatment of autoimmune diseases. The epigenetic regulation of FOXP3, encompassing DNA methylation, histone modifications, and post-translational modifications, governs the development and optimal suppressive function of Tregs. In addition, Tregs can also possess the ability to maintain homeostasis in diverse microenvironments through non-suppressive mechanisms. In this review, we primarily focus on elucidating the epigenetic regulation of Tregs as well as their multifaceted roles within diverse physiological contexts while looking forward to potential strategies involving augmentation or suppression of Tregs activity for disease management, particularly in light of the ongoing global COVID-19 pandemic.